The Influence of Lifestyle and Evolutionary Factors on Colorectal Cancer - Khayriyah Albahi,; Esra Oun,; Souad Salem, (AlQalam Journal of Medical and Applied Sciences, 2025)
This study aimed to estimate the incidence of colorectal cancer by age and sex, and evaluate the association between lifestyle and risk of colorectal cancer. A self-administered questionnaire was conducted on Sixty (60) Libyan patients aged 20-80 years (47 males and 13 females) at the National Institute for the Treatment of Oncology in Sabrata, during the period from February to July 2023. The results showed that 46.3% of CRC cases are female, while 53.7% of CRC cases are male. and 20.1% of CRC cases were aged less than 50 years, while 79.1% of CRC aged More than 50 years. The colorectal cancer injury happens mostly in men higher than in women, the disease mostly occurs in patients above 50 years old. The findings suggest that age and sex may influence CRC risk, underscoring the need for targeted screening and lifestyle interventions, particularly for older adults and men. Further research with larger samples is recommended to validate these associations.